Identifying resistance gene analogs associated with resistances to different pathogens in common beans - López, C.E.; Acosta, I.F.; Jara, Carlos E.; Pedraza García, Fabio; Gaitán Solís, Eliana; Gallego Sánchez, Gerardo J.; Beebe, Stephen E.; Tohme, Joseph M. (Scientific Societies, 2003)
A polymerase chain reaction approach using degenerate primers that targeted the conserved domains of cloned plant disease resistance genes (R genes) was used to isolate a set of 15 resistance gene analogs (RGAs) from common bean (Phaseolus vulgaris). Eight different classes of RGAs were obtained from nucleotide binding site (NBS)-based primers and seven from not previously described Toll/Interleukin-1 receptor-like (TIR)-based primers. Putative amino acid sequences of RGAs were significantly similar to R genes and contained additional conserved motifs. The NBS-type RGAs were classified in two subgroups according to the expected final residue in the kinase-2 motif. Eleven RGAs were mapped at 19 loci on eight linkage groups of the common bean genetic map constructed at Centro Internacional de Agricultura Tropical. Genetic linkage was shown for eight RGAs with partial resistance to anthracnose, angular leaf spot (ALS) and Bean golden yellow mosaic virus (BGYMV). RGA1 and RGA2 were associated with resistance loci to anthracnose and BGYMV and were part of two clusters of R genes previously described. A new major cluster was detected by RGA7 and explained up to 63.9% of resistance to ALS and has a putative contribution to anthracnose resistance. These results show the usefulness of RGAs as candidate genes to detect and eventually isolate numerous R genes in common bean.